Estimaçǎo de Fatores de Correção do Perímetro Escrotal para Idade e Peso Corporal em Touros Jovens da raça Nelore - Peña, Carlos Darío Ortiz; De Queiroz, Sandra Aidar [UNESP]; Fries, Luiz Alberto (My University, 2000)
This work studied the effects of age and weight on scrotal circumference (SC) of Nellore young breed bulls, and also estimated the SC correction factors (CF) for those effects. The information came from the Production Registry of the Paraguayan Nellore Breeders Association, obtained from 1986 to 1997 from 110 herds, totalling 7,458 observations. The regression coefficients that allowed the calculation of CF for SC were estimated by the least square methods. The model considered the contemporary group (animals born in the same year, season, herd, evaluated in the same day and from the same weaning and yearling feed management group), linear effect of age of the animal (days), and linear and quadratic effects of live weight at 570 days of age (W570). The age effect on SC was 0.0383(±0.0024) cm/day, and of W570 on SC, corrected for this age, was 0.0708(±0.0049) cm/kg, linear effect, and -0.0000413 (±0.0000074) cm/kg 2, quadratic effect. The age and live weight of the animals were important sources of variation to be removed from the SC as an indicator of sexual precocity in yearling bulls.
Estimation of Correction Factors of Scrotal Circumference for Age and Body Weight in Young Nellore Breed Bulls
Keywords: Beef cattle; Puberty; Regression coefficients; Reproductive performance; Sexual precocity